2014
DOI: 10.1242/jeb.100347
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and metabolic contributions to thermoregulation in freely swimming leatherback turtles at high latitudes

Abstract: Leatherback turtles in the Northwest Atlantic Ocean have a broad geographic range that extends from nesting beaches near the equator to seasonal foraging grounds as far north as Canada. The ability of leatherbacks to maintain core body temperature (T b ) higher than that of the surrounding water is thought to be a key element of their biology that permits them to exploit productive waters at high latitudes. We provide the first recordings of T b from freely swimming leatherbacks at a northern foraging ground, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 21 publications
(56 reference statements)
1
43
0
Order By: Relevance
“…The speeds of sea turtles (ectotherms, except for the leatherback turtle; ref. 22) were close to those of fishes without RM endothermy.…”
Section: Resultssupporting
confidence: 68%
“…The speeds of sea turtles (ectotherms, except for the leatherback turtle; ref. 22) were close to those of fishes without RM endothermy.…”
Section: Resultssupporting
confidence: 68%
“…In addition, more frequent diving and essentially continuous swimming generates endogenous heat (Bostrom et al, 2010). Casey et al (2014) reported that variation in leatherback body temperatures off Nova Scotia is best explained by time spent in surface waters, and that swimming activity also plays a role in maintaining a significant thermal gradient between leatherback body temperatures and ambient water temperatures. Therefore, although leatherbacks increase diving activity to achieve higher prey capture rates, which, in turn, increases the time they spend handling prey, this increased activity does not impose physiological costs that restricts their foraging effort, in contrast to theoretical predictions for diving predators (Thompson and Fedak, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Such analyses are rare for marine migratory species in general (e.g., Seminoff et al, 2006;Moll et al, 2007). Leatherback dives are shorter and shallower while foraging off Nova Scotia than during migration or while in lower latitudes, and feeding is restricted to daylight hours (James et al, 2005a;Casey et al, 2014;Hamelin et al, 2014). Hamelin et al (2014) used high-resolution dive data from three leatherbacks to show that turtles foraging in Atlantic Canada remain at or above the main thermocline, suggesting that prey resource distribution is associated with water mass.…”
Section: Ecology and Evolutionmentioning
confidence: 99%
“…A complicating factor in choosing a representative metabolic rate is that adult leatherbacks have elevated core temperatures (25-27°C) in cold (10.9-16.7°C) surface seawater (Frair et al, 1972;James and Mrosovsky, 2004;Casey et al, 2014) and regularly dive into nearfreezing water when foraging in Canadian waters (James et al, 2006). Current understanding is that an elevated core temperature is maintained by a combination of gigantothermy, insulation, plus muscular and visceral thermogenesis (Casey et al, 2014;Davenport et al, 2015).…”
Section: Leatherback Metabolic Ratesmentioning
confidence: 99%
“…Current understanding is that an elevated core temperature is maintained by a combination of gigantothermy, insulation, plus muscular and visceral thermogenesis (Casey et al, 2014;Davenport et al, 2015). As leatherbacks swim just as quickly in cold water as they do in the tropics (Davenport et al, 2015), it is likely that their FMRs are elevated at high latitude.…”
Section: Leatherback Metabolic Ratesmentioning
confidence: 99%